FUNCTION CLASS OF CHRONIC HEART FAILURE AND EFFICIENCY OF THERAPY AMIODARONE AND ITS COMBINATION WITH BETA-ADRENOBLOCKERS PERMANENT FORM OF ATRIAL FIBRILLATION AT PATIENTS WITH ARTERIAL HYPERTENSION AND ISCHEMIC HEART DISEASE - Makienko, N.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The comparison of efficiency of amiodarone and its combinations with metoprolol and carvedilol at 102 observed in in-patient department middle age of which was 64±9 years (M±sd) with permanent atrial fibrillation (AF), which complicated the IHD and AH flow according to initial FC ChHF. The patients were divided into the following groups: the first group - with II FC ChHF (40 patients) and the second group – with III FC ChHF (62 patients) with subdivision to sub-groups: sub-group A – patients taken amiodarone, A+M - amiodarone with metoprolol and A+C - amiodarone with carvedilol. By results of the AF research at patients with II FC ChHF more frequently flows on the background of soft moderate the AH or IHD degrees not higher than stable angina with II-III FC and is characterized by less duration, more higher general index quality of life (GIQL), and TP spectrum HRV at less HR. AF at patients with III FC ChHF flows more frequently on the background of moderate and heavy AH degrees and painless form IHD and is characterized by greater duration with less GIQL and TP spectrum HRV and greater HR. At AF patients with II FC ChHF initial monotherapy of amiodarone with joining of beta-adrenoblockers (BAB) according to clinical indications is possible more frequently, while at patients with III FC ChHF it is expedient to begin the therapy by combination of amiodarone with BAB, hence for patients with AF combination of amiodarone with carvedilol is more preferable than combinations with metoprolol.